Sulfur elimination by oxidative desulfurization with titanium-modified SBA-16. - Rivoira , Lorena Paola; Vallés , Verónica Alejandra; Ledesma , Brenda Cecilia; Ponte , María Virginia; Martínez , María Laura; Anunziata , Oscar Alfredo; Beltramone, Andrea Raquel; Anunziata , Oscar Alfredo; Martínez , María Laura; Ponte , María Virginia; Ledesma , Brenda Cecilia; Vallés , Verónica Alejandra (Univesidsad Tecnológica Nacional., 2015)
TiO2-modified mesoporous SBA-16 and titanium-substituted mesoporous SBA-16 were developed and tested in the oxidative desulfurization (ODS) of dibenzothiophene prevailing in liquid fuel. Pure TiO2 was used as reference. The titania-based catalysts were characterized by chemical analysis, XRD, EDX and TEM. The titanium state as tetrahedral (in Ti-SBA-16 sample) or octahedral (in TiO2/SBA-16 sample) coordination surrounding in the silicate matrix was determined by XPS, UV–vis DRS, FTIR, Raman and XANES. We assessed the impact exerted on performance of different reaction variables, including (nature and amount of the active catalytic species, phase system, molar ratio of oxidant H2O2 and DBT, reaction temperature, nature of the substrate and reuse of catalysts). In addition, we carried out a kinetic study and the activation energy was determined. We achieved 90% of S removal from a 0.2 wt.% dibenzothiophene solution at 60 ◦C in less than 1 h of reaction. The best catalytic results are obtained with high exposed surface of nanometric TiO2 species of TiO2/SBA-16 sample. The activated catalyst is very active in ODS reaction and can be reused four times with no loss in activity.
Keywords: Ti-containing SBA-16; Ti02; Ti incorporation method; ODS; Reaction kinetics